Analisis Pengaruh Net Profit Margin (NPM), Gross Profit Margin (GPM), Return On Asset (ROA), Dan Return On Equity (ROE), Terhadap Harga Saham Pada PT Gajah Tunggal Tbk - Syaiful Ahyar; Muhamad Rimawan (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to find out whether Net Profit Margin (NPM), Gross Profit Margin (GPM), Return on Assets (ROA), and Return on Equity (ROE) have an effect on share prices at PT Gajah Tunggal Tbk. This type of research is associative research with a quantitative approach. The population used in this research is the financial statements of PT Gajah Tunggal Tbk for 32 years, with a sample of 10 years obtained using purposive sampling technique. The data analysis techniques used in this research are the classical assumption test, multiple linear analysis, correlation and determination coefficient test, t test, and f test. The results of research using the t test partially show that the variables Net Profit Margin (X1), Gross Profit Margin (X2), and Return on Equity (X4) have no effect on stock prices. Meanwhile, the variable Return on assets (X3) influences share prices.